Incidental Finding of Dextrocardia with Situs Inversus in a 59-Year-Old Man - Edzie, Emmanuel Kobina Mesi (Case Rep Radiol, 2019)
Dextrocardia with situs inversus is a rare congenital anomaly, which is characterized by right-sided heart apex and inversely rotated visceral organs of the abdomen. We report an unusual case of dextrocardia with situs inversus in a 59-year-old man, referred for a pelvic ultrasound scan because of symptoms of lower urinary tract obstruction and after a fairly normal prostate specific antigen (PSA) value. A diagnosis of enlarged prostate gland with a prominent median lobe and significant residual urine volume was made, which necessitated the examination of the kidneys for hydronephrosis, resulting in the incidental finding of situs inversus. On further investigation, the diagnosis of dextrocardia with situs inversus was made. Physicians should look out for this anomaly primarily because it may be associated with other conditions like primary ciliary dyskinesia so appropriate interventions are offered to reduce morbidities and mortality.